Emerging treatments in type 2 diabetes: focus on canagliflozin - Rosiak M; Grzeszczak S; Kosior DA; Postuła M (Dove Medical Press, 2014)
Marek Rosiak,1,2 Susanna Grzeszczak,2 Dariusz A Kosior,2,3 Marek Postuła1,2 1Department of Cardiology and Hypertension, Central Clinical Hospital, the Ministry of the Interior, Warsaw, Poland; 2Department of Experimental and Clinical Pharmacology, Medical University of Warsaw, Poland; 3Mossakowski Medical Research Centre, Polish Academy of Sciences, Warsaw, Poland Abstract: Type 2 diabetes mellitus (T2DM) is a prevalent metabolic disorder, which affects more than 300 million people globally. The common effect of uncontrolled diabetes is the state of hyperglycemia, which results from beta-cell dysfunction as well as insulin resistance, which is accompanied with microvascular and macrovascular complications. As hyperglycemia defines diabetes, glycemic control is fundamental to the management of diabetes. Sodium glucose co-transporter 2 inhibitors (SGLT2) are a new group of oral antidiabetic medications that act by blocking the reabsorption of glucose, causing it to be excreted in the urine. Canagliflozin was the first SGLT2 inhibitor to be approved in the US by the Food and Drug Administration for the treatment and control of T2DM and on September 19, 2013, the Committee for Medicinal Products for Human Use of the European Medicines Agency adopted a positive opinion, recommending the granting of a marketing authorization for the medicinal product Invokana®. Canagliflozin is a SGLT2 inhibitor, which acts upon the proximal tubules of the kidneys and reduces the renal threshold for glucose. It is highly selective, binding 250 times more potently to SGLT2 than sodium glucose co-transporter 1 inhibitor. This action allows a higher amount of glucose to be excreted within the urine, causing the patient's plasma glucose level to be decreased and indirectly causing weight loss. Among the most common adverse events are hypoglycemia, headache, nausea, female genital and urinary tract infections, nasopharyngitis, and transient postural dizziness. Given its high efficacy in reducing hyperglycemia and good safety profile as either monotherapy or an add-on treatment to metformin, sulfonylureas, or insulin, canagliflozin seems to be a promising antihyperglycemic drug. Nevertheless, further large-scale and long-term studies should be conducted to evaluate the impact of canagliflozin on cardiovascular risk in T2DM patients. Keywords: hyperglycemia, SGLT2 inhibitor, hypertension, dapagliflozin, insulin resistance, obesity, blood pressure, weight loss